Estudo da frequência e perfil epidêmico-sorológico da toxoplasmose ocular em pacientes atendidos no Ambulatório de Oftalmologia do Hospital Universitário Onofre Lopes no município de Natal, Rio Grande do Norte - Mendes, Norma Helena Duarte (2011)
Toxoplasmosis, provoked by the intracellular parasite Toxoplasma gondii, is one of the most prevalent parasitoses in the world. In humans, transmission occurs by three evolutionary forms of the parasite: oocysts, tissue cysts and tachyzoites. Wild and domestic felines are definitive hosts. The ocular form of toxoplasmosis can be of congenital origin with early or late clinical manifestations, or acquired after birth. T. gondii is considered the main culprit for most cases of infectious uveitis. This study aimed at assessing ocular toxoplasmosis, relating it to factors associated to the patient s lifestyle and describing the epidemic-serological and clinical profile of affected individuals. A cross-sectional study was conducted with a population of 159 patients. Univariate analysis (odds ratio) was used to evaluate the data, with a confidence interval of 95% and p-value < 0.05. A prevalence of 4% of ocular toxoplasmosis was observed in the population of patients treated at an ophthalmological clinic. Of patients directly examined by immunoenzymatic assay (MEIA-AxSYM®- Microparticle Enzyme Immune Assay), considering only uveitis, a frequency of anti-T. gondii of 73%, most of whom exhibited titulation between 40-99 UI IgG/mL. With respect to location of ocular lesions, bilaterality was observed in 57% of patients assessed by the ophthalmoscopy technique. When compared with the results of an active search of medical records, a similarity in ocular toxoplasmosis (74%) and bilateral lesion location (55%) was observed. Type I lesion was the most frequent type observed, with intraocular disposition in the macula. An epidemiological survey revealed that direct contact with cats; consuming raw or poorly cooked meat and direct contact with the soil were significantly associated with greater likelihood of acquiring ocular toxoplasmosis. Sample characterization in relation to age range was significant for patients between 31 and 40 years [χ², chi-square test (p = 0.04)], but population traits such as schooling, sanitary district, and monthly income were not significant. Results confirm that ocular toxoplasmosis is widely distributed in the metropolitan area of Natal, Brazil, with significant prevalence of ocular lesions provoked by T.gondii. It is suggested that sanitary authorities exert greater control in order to minimize the risk of toxoplasmic infection, mainly in pregnant women.